2011
DOI: 10.1123/jpah.8.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Cost and Speech Quality While Using an Active Workstation

Abstract: Background:The effect of active workstation implementation on speech quality in a typical work setting remains unclear.Purpose:To assess differences between sitting, standing, and walking on energy expenditure and speech quality.Methods:Twenty-two females and 9 males read silently, read aloud, and spoke spontaneously during 3 postural conditions: sitting, standing, and walking at 1.61 km/h. Oxygen consumption (VO2), blood pressure, and rating of perceived exertion (RPE) were obtained during each condition. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 28 publications
8
45
0
Order By: Relevance
“…Even though the durations were in line with other studies (e.g. Cox et al 2011;Elmer and Martin 2014;Funk et al 2012), another possible limitation was that the duration of tasks may not be representative for all task durations during every-day office work, and therefore may limit transferability of some of the results. Further research with a longer duration of tasks and in-field settings is required to investigate the optimal duration and intensity for using these workstations in a realistic work environment setting.…”
Section: Resultsmentioning
confidence: 82%
“…Even though the durations were in line with other studies (e.g. Cox et al 2011;Elmer and Martin 2014;Funk et al 2012), another possible limitation was that the duration of tasks may not be representative for all task durations during every-day office work, and therefore may limit transferability of some of the results. Further research with a longer duration of tasks and in-field settings is required to investigate the optimal duration and intensity for using these workstations in a realistic work environment setting.…”
Section: Resultsmentioning
confidence: 82%
“…Of the 4 studies that measured energy 213 expenditure using indirect calorimetry, 3 found that a standing pos-214 ture resulted in significant increases varying from 4.1 kcal/h to 20.4 215 kcal/h in each study(Beers et al, 2008;Cox et al, 2011;Q20 Reiff et al, 216 2012). The single study that did not find a difference in energy ex-217 penditure had a very low rating of methodological quality owing 218 primarily to a lack of detail in the manuscript (Speck and Schmitz, crease while standing of 8.4 ± 4.8 beats/min (bpm) on average 221 (Beers et al, 2008; Q21Straker et al, 2009;Cox et al, 2011). BP was 222 measured in only one study and also showed a significant increase 223 in systolic BP from 123 ± 3 mm Hg to 124 ± 3 mm Hg while stand-224 ing, as well as an increase in diastolic BP from 76 ± 3 mm Hg to 225 82 ± 3 mm Hg while standing.…”
mentioning
confidence: 96%
“…BP) during a single assessment of the standing posture(Beers et al, 211 2008;Cox et al, 2011;Levine and Miller, 2007; Q19 Reiff et al, 2012; 212 Speck and Schmitz, 2011). Of the 4 studies that measured energy 213 expenditure using indirect calorimetry, 3 found that a standing pos-214 ture resulted in significant increases varying from 4.1 kcal/h to 20.4 215 kcal/h in each study(Beers et al, 2008;Cox et al, 2011;Q20 Reiff et al, 216 2012).…”
mentioning
confidence: 99%
“…The walking workstation may increase daily energy expenditure, [21][22][23][24] and has also been tested to examine its effect on typing speed, cognition, attention, motor skill, and speech quality. 21,25,26 Depending on the nature of the office work, the walking workstation could prove effective at reducing sedentary behavior and improving health in the workplace without adversely affecting job function. 23,24 While a single bout of exercise at the low end of the moderateintensity domain (~3.5 METs) has been shown to reduce postexercise BP, 10,13 walking at 3.5 METs (~3 mph), 27 would not be feasible on a walking workstation.…”
mentioning
confidence: 99%